Analysis of Internal Control and Financial Governance on the Performance of the Simo Djojo Makmur Village-Owned Enterprise (BUMDes) in Simoketawang Village, Sidoarjo Regency - Mario Febrianus Rion Gan; Benedict Robin Lambur; Francis Femas San; Aloisius Hama (International Journal of Business and Quality Research, 2026)
This study aims to analyze the effect of Internal Control and Financial Governance on the financial performance of the Simo Djojo Makmur Village-Owned Enterprise (BUMDes) in Simoketawang Village, Sidoarjo Regency, which employs 44 staff members. Internal Control functions as a mechanism that helps the organization manage and direct resources effectively and efficiently to achieve operational and strategic objectives. Meanwhile, Financial Governance serves as a guideline for creating transparency, accountability, and integrity in organizational management, which is essential for enhancing performance and stakeholder trust.The method used in this study is a quantitative analysis with a multiple linear regression approach. This technique is employed to examine the influence of the independent variables, namely Internal Control and Financial Governance, on the dependent variable, which is financial performance.The results of the analysis indicate that both Internal Control and Financial Governance have a positive and significant effect on financial performance. Effective Internal Control supports the organization in evaluating and improving ineffective operations, while the implementation of Financial Governance enhances the quality of financial management, contributing to the efficiency and effectiveness of financial performance.